2001
DOI: 10.1002/app.1292
|View full text |Cite
|
Sign up to set email alerts
|

Photoaging and stabilization of rigid PVC/wood‐fiber composites

Abstract: Ultraviolet (UV) weathering performance of unpigmented and rutile titanium dioxide pigmented rigid polyvinyl chloride (PVC)/wood-fiber composites has been studied. The composite samples were manufactured by dry-blending PVC, wood fibers, and other processing additives in a high-intensity mixer. The dry-blended compounds were extruded and compression molded into panel samples. The manufactured samples were artificially weathered using laboratory accelerated UV tests. Composite samples were exposed to 340-nm flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
92
0
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 133 publications
(95 citation statements)
references
References 20 publications
1
92
0
2
Order By: Relevance
“…Studies on the factors affecting on the properties of WPC under weathering conditions have focused on various aspects, such as weathering conditions (e.g. moisture, temperature, and biological decay) [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], wood content, processing method, weathering condition, and type and content of UV absorbers and pigments [3][4][5][6][7][8][9][10][11][12][13][14]. The presence of wood has been found to accelerate the photodegradation of WPC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on the factors affecting on the properties of WPC under weathering conditions have focused on various aspects, such as weathering conditions (e.g. moisture, temperature, and biological decay) [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], wood content, processing method, weathering condition, and type and content of UV absorbers and pigments [3][4][5][6][7][8][9][10][11][12][13][14]. The presence of wood has been found to accelerate the photodegradation of WPC.…”
Section: Introductionmentioning
confidence: 99%
“…Works by Stark and Matuana [3,4] showed that wood particles accelerated the oxidation reaction at the surface of wood/high density polyethylene (WPE) composite, to a greater extent than that of neat high density polyethylene (HDPE). In the case of wood/polyvinyl chloride (WPVC) composites, the presence of wood strongly accelerated the photodegradation of PVC [5][6][7] and interfered with the function of a UV absorber [7]. The chromophore groups or carbonyl groups in lignin as a component of wood accelerated the photodegradation of polymer matrix with enhancing absorption of UV light on the WPC surface.…”
Section: Introductionmentioning
confidence: 99%
“…Estudos de fotodegradação de compósitos poliméricos mostram que alguns componentes retardam, mas também podem acelerar o processo degradativo do outro componente. Um exemplo é o efeito fotodeteriorativo ao se inserir fibra ou pó de madeira em uma matriz de PVC rígido [7,8] . Contudo, esse mesmo tipo de aditivo impediu a formação de reticulações em estágios iniciais de fotodegradação quando inserido em matriz de PEAD, neste caso através de um impedimento físico [9] .…”
Section: Introductionunclassified
“…Durability of natural fibre composites upon exposure to UV-light is of particular concern as UV-light can cause the changes in the surface chemistry of the composites commonly known as photodegradation [5,6]. The degradation ranges from mere surface discoloration affecting the aesthetic appeal in indoor applications to extensive loss of mechanical properties [7,8].…”
Section: Introductionmentioning
confidence: 99%